The Development of Women’s Rights Under Secular Regimes: Tunisia - Simon, Rachel (Colloquium: The Political Science Journal of Boston College, 2017)
With increasing tensions in the Middle East, the rights of Middle Eastern women have become a contentious topic in Western political and cultural discourse. Spurred by the seeming success of secular women’s rights movements in the West, many Westerners are pushing for the secularization of Middle Eastern governments. This paper analyzes the effectiveness of this theory by evaluating the development of women’s rights in Tunisia, a country in the Middle East, which has in fact taken on predominantly secular approaches to government. Tunisia has long led the movement towards gender equality in the Middle East, and remains at the forefront of women’s rights in the Arab world today, providing support for this Western ideology. However, Tunisia’s secular governments have significantly hindered the progression of women’s rights as well. Tunisia’s secular regimes, often authoritarian, have appropriated “state feminism” to gain popular support without authentically empowering Tunisian women, leaving women’s rights in peril if the regimes fall. Moreover, these secular regimes have augmented Islamic extremism, which not only endangers the lives of Tunisian women, but has also created a precarious divide between Tunisian women. Thus, the Western prescription of secularism is not an all-encompassing solution to inequality in the Middle East.